Sound Absorption Properties of Acoustical Particleboard with Sawdust and Rice Straw - Mohd Azme, Ahmad Farhan; Abdul Rohani, Muhammad Iqbal; Sharifuddin, Muhammad Shaqeel; Aslila Abd. Kadir, (Multidisciplinary Applied Research and Innovation, 2024)
Agricultural and industrial waste are typically disposed of by burning. As a result, it will indirectly contribute to the release of carbon dioxide into the atmosphere, further polluting the environment. Previous research has found that these waste materials have the potential to be used in the production of acoustic panel boards. This project investigates the use of agricultural waste rice straw and industrial waste sawdust as basic materials in the production of acoustic panel boards. Both of these materials will be reinforced with an epoxy resin adhesive. The tests such as water absorption test, bending test and acoustical properties will be carried out and will be compared with the standard for particle board which is JIS A 5908 (2003), ASTM D1037 and ISO 11654 (1997). The sandwich particleboard made from coarse rice straw and sawdust was the best and recommended for the manufacturing process. This sandwich particleboard was a higher sound absorption coefficient than the other sample. The recommended sandwich particle board made from rough rice straw and sawdust has been defined in terms of its ability to absorb sound, be durable, and can partially or totally replace wood particle board and insulation board in wood construction.